2022
DOI: 10.1007/s13365-021-01046-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the balloon analog risk task to neurocognitive impairment differs by HIV serostatus and history of major depressive disorder

Abstract: HIV and major depressive disorder (MDD) commonly co-occur and are both linked to greater risk-taking behavior, possibly due to neurocognitive impairment (NCI). The present study examined the concordance of the Balloon Analog Risk Task (BART), a gold standard measure of risk-taking propensity, with NCI and real-world sexual risk behaviors in PWH with comorbid MDD. Participants included 259 adults, stratified by HIV serostatus (HIV + /HIV −) and lifetime MDD (MDD + /MDD −), who completed neuropsychological testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…The same attention bias can also be observed in adolescent depression (4). Neuropsychological studies have shown that attention function had been also impaired in patients with remitting MDD (5,6). However, the neurobiological mechanism underlying the symptoms of MDD has not been fully understood.…”
Section: Introductionmentioning
confidence: 84%
“…The same attention bias can also be observed in adolescent depression (4). Neuropsychological studies have shown that attention function had been also impaired in patients with remitting MDD (5,6). However, the neurobiological mechanism underlying the symptoms of MDD has not been fully understood.…”
Section: Introductionmentioning
confidence: 84%